THE INFLUENCE OF STICK FIGURES MEDIA ON ARABIC WRITING PROFICIENCY: AN EXPERIMENTAL STUDY AT MTsN 3 TANAH DATAR / ØªØ£Ø«ÙŠØ± ÙˆØ³ÙŠÙ„Ø© Ø¹ØµØ§ Ø§Ù„Ø£Ø±Ù‚Ø§Ù… Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø©: Ø¨ØØ« ØªØ¬Ø±ÙŠØ¨ÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø§Ù„Ø«Ø§Ù„Ø«Ø© ØªØ§Ù†Ù‡ Ø¯Ø§ØªØ§Ø± - Nofrizal Nofrizal; Akhyar Hanif; Ferki Ahmad Marlion; Kamaluddin Kamaluddin; Amrina Amrina (IAIN Batusangkar, Indonesia, 2022)
The purpose of this study was to determine the effect of Stick Figure media on students’ Arabic writing skills at MTsN 3 Tanah Datar. The researcher used an experimental research method with a quasi-experimental Posttest Only Nonequivalent Control Group design. The sample of the research was 54 students chosen at random, who were then divided into two groups: the experimental group of 27 students and the control group of 27 students. Data collection technique was a test. Each group received a pre and post test.The t test was used to analyze the data. Based on the research findings, to is greater than tt, namely 0.46> 0.273, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Based on the hypothesis test, it can be concluded that the use of Stick Figures media has an effect on students' Arabic writing skills at MTsN 3 Tanah Datar. As a result, the use of Stick Figure media in particular, and instructional media in general, can have an impact on students’ learning outcomes. Therefore, Arabic teachers are expected to always select and use appropriate media when teaching Arabic.